PENGARUH PENERAPAN PEMBELAJARAN MOBILE LEARNING TERHADAP PENINGKATAN HASIL BELAJAR EKONOMI - Imam Munandar (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
The Information and Communication Technology is growing rapidly at this time. So, it sues all levels of society to follow that growth, so does education world should take advantage of current developments. The research objective wassee the effect ofmobile learning that utilizesadvances in information technology and communication on that improvement in learning outcomes on economic subjects using social media Edmodo. This research was conducted in SMA Negeri 4 Kota Tangerang Selatan with quasi experimental designby two sample groups which are all experimental class. The results of this study showed a significant improvement on the learning outcomes of the two experimental classes shown in the n-gain test, whereas the hypothesis test results explained that the improvement of the two experimental classes was the same, and based on the triangulation method of observation, the questionnaire and the interview showed the results which is positive.